Effects of isocoumarins isolated from Paepalanthus bromelioides on mitochondria: Uncoupling, and induction/inhibition of mitochondrial permeability transition - Calgaro-Helena, A. F.; Devienne, K. F.; Rodrigues, T.; Dorta, D. J.; Raddi, MSG; Vilegas, Wagner [UNESP]; Uyemura, S. A.; Santos, A. C.; Curti, C. (Elsevier B.V., 2006)
Isolated mitochondria may undergo uncoupling, and in presence of Ca2+ at different conditions, a mitochondrial permeability transition (MPT) linked to protein,thiol oxidation, and demonstrated by CsA-sensitive mitochondrial swelling; these processes may cause cell death either by necrosis or by apoptosis. Isocoumarins isolated from the Brazilian plant Paepalanthus bromelioides (Eriocaulaceae) paepalantine (9,10-dihydroxy-5,7-dimethoxy-1H-naptho(2,3c)pyran-1-one), 8,8'-paepalantine dimer, and vioxanthin were assayed at 1-50 mu M on isolated rat liver mitochondria, for respiration, MPT, protein thiol oxidation, and interaction with the mitochondrial membrane using 1,6-diphenyl-1,3,5-hexatriene (DPH). The isocoumarins did not significantly affect state 3 respiration of succinate-energized mitochondria; they did however, stimulate 4 respiration, indicating mitochondrial uncoupling. Induction of MPT and protein thiol oxidation were assessed in succinate-energized mitochondria exposed to 10 mu M Ca2+; inhibition of these processes was assessed in non-energized organelles in the presence of 300 mu M t-butyl hydroperoxide plus 500 mu M Ca2+. Only paepalantine was an effective MPT/protein thiol oxidation inducer, also releasing cytochrome c from mitochondria; the protein thiol oxidation, unlike mitochondrial swelling, was neither inhibited by CsA nor dependent on the presence of Ca2+. Vioxanthin was an effective inhibitor of MPT/protein thiol oxidation. All isocoumarins inserted deeply into the mitochondrial membrane, but only paepalantine dimer and vioxantin decreased the membrane's fluidity. A direct reaction with mitochondrial membrane protein thiols, involving an oxidation of these groups, is proposed to account for MPT induction by paepalantine, while a restriction of oxidation of these same thiol groups imposed by the decrease of membrane fluidity, is proposed to account for MPT inhibition by vioxanthin. (c) 2006 Published by Elsevier B.V..
Keywords: isocoumarins; paepalantine; liver mitochondria; uncoupling; mitochondrial permeability transition; permeability transition pore; protein thiol oxidation; mitochondrial membrane fluidity